PERAN POLISI LALU LINTAS DALAM MENINDAK PELANGGARAN PEMAKAIAN HELM STANDAR DI POLRES LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Herma Mela Fadjri; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research title is the Role of Traffic Police against the infraction of Standard Helmet usage at the Police resort Lima Puluh Kota of west sumatera Province. Basically, the people of Lima Puluh Kota have motorcycle and they have already known to use the standard helmet. This research is using a quantitative descriptive method . With aim to collect information and data concerning infraction of Standard Helmet usage, then analyze the data according to the fundamental problem. This research consists of two sources, those areprimary and secondary data source. The informant key of this research is the police. The theory used in this research is the theory of role, The finding of this researchis that people generally have known the rule of standard helmet usage.However, the awareness of self-safety is still less.In addition, the police have run their duty and role seen from the socialization which is often conducted. Although it is not maximal yet, but some of people have already known that standard helmet usageis an obligation.Keywords: Roles, Standard Helmet, Collision, and Traffic Police